Faktor-Faktor yang Mempengaruhi Terjadinya Rheumatoid Arthritis pada Lansia - Yuliyanti, Sasteri; Lestari, Rapita; Pebriani, Emi (ProHealth Journal, 2024)
The elderly also often experience degenerative diseases that reduce immunity, hypertension, heart disease, stroke, diabetes mellitus, oral problems and Rheumatoid Arthritis joint disease. Some of the factors that affect the occurrence of Rheumatoid Arthritis are gender, genetics, nutritional status, and knowledge. Aim to identify the factors that affect the occurrence of Rheumatoid Arthritis in the elderly in the Working Area of the Telaga Dewa Health Center, Bengkulu City in 2024. This study uses descriptive analysis with a cross sectional approach. The data used is primary data and secondary data. To find out gender, genetics, nutritional status, and knowledge data using questionnaires. The data wasanalyzed using the chi square test. The results of the study were obtained by most of the 40 (65.6%) respondents whoexperienced rheumatoid arthritis, most of the respondents 39 (63.9%) were female, more than 36 (59%) respondents had a genetic history, as many as 11 (18%) respondents had poor nutritional status, and as many as 23 (37.7%) respondents had less knowledge. The results of statistical tests found that there was a relationship between gender (p= 0.000), genetics (p= 0.006), nutritional status(p= 0.01), and knowledge (p= 0.004) with the occurrence of rheumatoidarthritis. The conclusion in this study is that rheumatoid arthritis is caused by various factors, namely genetic factors,gender factors, nutritional status factors and knowledge factors.